The Effect of Preoperative Short Course of Oral Steroids followed by Postoperative Topical Nasal Steroids Sprays on Nasal Polyp Recurrence after Endoscopic Nasal Polypectomy - Mahmud, Khaled; Faruque, MN; Faisal, KA (Journal of Dhaka National Medical College & Hospital, 2012)
Objective: To evaluate the effect of preoperative short course of oral steroids followed by postoperative topical nasal steroids sprays on nasal polyp recurrence after endoscopic nasal polypectomy. Methods: Forty eight patients of both genders with symptoms and signs of nasal polyps were included in this prospective study between January 2006 and December 2009. Their ages ranged between 18 and 60 years. The sample was divided into two groups. Group I constituted 24 patients treated by endoscopic nasal polypectomy without oral and local steroid therapy. Group II consisted of 24 patients also treated by endoscopic nasal polypectomy but received preoperatively 60mg prednisolone tablets daily for one week and postoperatively topical nasal steroid spray (Mometasone furoate suspension) for three months. All patients were followed up for at least one year. Recurrence of nasal polyps was assessed endoscopically at three, six and 12 months after surgery. Any evidence of nasal polyps-formation of whatever size was considered as recurrence. Results: Forty eight patients (32 males and 16 females) with sinonasal polyposis were included in this study. Male to female ratio was 2:1. Patients age ranged from 18 to 60 years; median age was 42 years. Recurrence rates at three, six and 12 months after surgery for the first group of patients were 8.33% (2 patients), 25% (6 patients) and 41.6% (10 patients) accordingly, while the recurrence rates for the second group were 4.1% (1 patient), 8.3% (2 patients) and 12.5% (3 patients) accordingly. Conclusions: Preoperative short course of oral steroid followed by postoperative nasal steroid spray show significant reduction in the recurrence rate of nasal polyps after endoscopic nasal polypectomy. DOI: http://dx.doi.org/10.3329/jdnmch.v17i2.12215 J. Dhaka National Med. Coll. Hos. 2011; 17 (02): 40-43